2004
DOI: 10.1023/b:wate.0000049187.35869.7d
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of AlCl3Additions on Rhizosphere Soil and Fine Root Chemistry of Sugar Maple (Acer Saccharum)

Abstract: Abstract. Increased Al mobilization and Ca and Mg leaching have been linked to nutritional imbalances in sugar maple across the northeastern US and Canada. The susceptibility of sugar maple fine roots to Al stress is poorly understood, in part because roots respond to Al stress by altering the chemistry of the rhizosphere. AlCl 3 was applied to plots of sugar maple at the Hubbard Brook Experimental Forest, NH. After two years of treatment, we sampled fine roots of sugar maple, rhizosphere soil, and bulk soil i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Al 3+ , Mn 2+ ) will increase [74], [75]. Those metals show very high degrees of toxicity for many plants [76], [77], and thus affect root respiration [14]. In this study, the fine root biomass in the warm-wet season in the MF and the BF revealed a negative response to the increasing level of SAR (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Al 3+ , Mn 2+ ) will increase [74], [75]. Those metals show very high degrees of toxicity for many plants [76], [77], and thus affect root respiration [14]. In this study, the fine root biomass in the warm-wet season in the MF and the BF revealed a negative response to the increasing level of SAR (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…The remained samples were air-dried and used to measure pH (soil : water = 1 : 2.5) and the nutrient contents. Exchangeable elements (K + , Ca 2+ , Mg 2+ ) were extracted with 1 mol/L NH 4 OAC 18 , and exchangeable Al 3+ was extracted with 1 mol/L KCl (soil : solution = 1 : 10) 46 . All base cations were determined by inductively coupled plasma optical emission spectrometer (Perkin Elmer, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The lowest availability was seen in the harvest stage of maize. When looking into the significant differences among the rhizosphere and non rhizosphere soil, the former was pertained to show 5.8% more P availability than the later irrespective of the crop growth period which was in line with Phillips and Yanai, (2004). Increased organic matter decomposition caused by increased microbial populations in the MILASHECHKINA ET AL S625 rhizosphere might have resulted in higher nutrient concentrations in the rhizosphere solution were found in alignment with Leyval and Berthelin, (1993); Drever and Vance, (1994); Wang and Zabowski, (1998).…”
Section: Resultsmentioning
confidence: 54%